2010
DOI: 10.2340/00015555-0867
|View full text |Cite
|
Sign up to set email alerts
|

Itch in Ethnic Populations

Abstract: Racial and ethnic differences in the prevalence and clinical characteristics of itch have rarely been studied. The aim of this review is to highlight possible associations between ethnicity and different forms of chronic itch. We provide a current review of the prevalence of different types of itch in ethnic populations. Genetic variation may significantly affect receptors for itch as well as response to anti-pruritic therapies. Primary cutaneous amyloidosis, a type of pruritic dermatosis, is particularly comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 76 publications
1
40
0
1
Order By: Relevance
“…Repeatibility variation in recording CI should be kept to minimum. The study of CI is complicated by multiple factors such as age, environment, level of education and literacy rate, social, cultural and psychological factors (10,22,23,30) (Fig. 1).…”
Section: Important Issues Of Itch Questionnairesmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeatibility variation in recording CI should be kept to minimum. The study of CI is complicated by multiple factors such as age, environment, level of education and literacy rate, social, cultural and psychological factors (10,22,23,30) (Fig. 1).…”
Section: Important Issues Of Itch Questionnairesmentioning
confidence: 99%
“…In particular, the impact of ethnicity on CI has received minimal attention. Itch intensity ratings are likely to differ between patients of varying ethnic and cultural backgrounds (30). Further, the distribution of underlying aetiologies causing CI varies substantially between countries (23).…”
Section: Important Issues Of Itch Questionnairesmentioning
confidence: 99%
“…Based on data from the National Burn Registry and the US Census data, African Americans are 1.5 times as likely to experience burn injury compared to European Americans [2; 8], and in other clinical settings African Americans have been shown to experience a greater burden of pain and itch relative to European Americans [14; 17; 50; 56]. Some of this disparity in pain and itch outcomes is likely due to the markedly greater socioeconomic disadvantage experienced by African Americans [25; 41; 64]; however, evidence from other health conditions characterized by chronic pain and/or itch suggests that differences in health outcomes between African Americans and European Americans may not be due to socioeconomic differences alone [46; 52; 56; 64].…”
Section: Introductionmentioning
confidence: 99%
“…Some of this disparity in pain and itch outcomes is likely due to the markedly greater socioeconomic disadvantage experienced by African Americans [25; 41; 64]; however, evidence from other health conditions characterized by chronic pain and/or itch suggests that differences in health outcomes between African Americans and European Americans may not be due to socioeconomic differences alone [46; 52; 56; 64]. …”
Section: Introductionmentioning
confidence: 99%
“…In view of the growing populations of immigrants in both Western Europe and the USA, it is important to acknowledge the existence of significant differences in skin physiology. Research has shown different prevalences of itch as a symptom in different ethnic groups, and data show that differing levels of clinical importance are placed upon itch across ethnicities 1 . In Norway, healthy male immigrants from East Asia, the Middle East, and North Africa report the presence of itch significantly more frequently than Norwegians and immigrants from Western countries 2 .…”
Section: Introductionmentioning
confidence: 99%